2023
DOI: 10.1017/s0033291723001861
|View full text |Cite
|
Sign up to set email alerts
|

Predicting long-term outcome in anorexia nervosa: a machine learning analysis of brain structure at different stages of weight recovery

Dominic Arold,
Fabio Bernardoni,
Daniel Geisler
et al.

Abstract: Background Anorexia nervosa (AN) is characterized by sizable, widespread gray matter (GM) reductions in the acutely underweight state. However, evidence for persistent alterations after weight-restoration has been surprisingly scarce despite high relapse rates, frequent transitions to other psychiatric disorders, and generally unfavorable outcome. While most studies investigated brain regions separately (univariate analysis), psychiatric disorders can be conceptualized as brain network disorders character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This may also explain our divergent findings for the insula as well. Several previous studies observed significant alterations in gray matter in the insula in individuals with AN, which we were likely not powered to observe (Arold et al, 2023;Frank et al, 2013;Lavagnino et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This may also explain our divergent findings for the insula as well. Several previous studies observed significant alterations in gray matter in the insula in individuals with AN, which we were likely not powered to observe (Arold et al, 2023;Frank et al, 2013;Lavagnino et al, 2018).…”
Section: Discussionmentioning
confidence: 84%
“…While the etiology of atypical AN and AN is still unclear, studies utilizing neuroimaging approaches have shown that the severe caloric restriction and concomitant reduction in body weight have a negative impact (i.e., reduction) on cortical gray matter (Arold et al, 2023;Bahnsen et al, 2022;King et al, 2018). The recent meta-analysis conducted by Walton and colleagues from the Enhancing Neuro Imaging Genetics through Meta Analysis (ENIGMA) Eating Disorders Working Group (2023) provides the most conclusive evidence of the negative impact of the illness on cortical gray matter thus far (Walton et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In another study published in 2024, researchers were able to successfully distinguish between AN and BN utilizing ML models based on diffusion tensor images (DTI), with the left middle temporal gyrus (MTG_L) and the left superior temporal gyrus (STG_L) suggested as potentially useful neuroimaging biomarkers (Zheng et al, 2024). In a further ML study that sought to predict longerterm outcomes in patients with AN using analysis of regional grey matter (GM) structure at different stages of weight recovery, scientists showed that underweight and partially weight restored (WR) patients could be differentiated from healthy controls (Arold et al, 2023). Of interest, the ML-based risk score was a predictor of future outcomes, and partially WR patients who had poor outcomes showed alterations in regions of the brain with greater functional connectivity, which could not be fully explained by body mass index.…”
Section: Imaging Datamentioning
confidence: 99%